KEBIJAKAN KURIKULUM PENDIDIKAN DI SD IT FADILAH PEKANBARU: Kebijakan Pendidikan - fika, Fika Amelia (Fakultas Studi Islam Universitas Muhammadiyah Riau, 2022)
Abstrak The curriculum is an important part of the continuity of the teaching and learning process. So that if education does not use the curriculum in learning, it can be ensured that learning runs inconsistently. The purpose of this research is to gain or add new knowledge or discoveries. And as proof of testing the truth that already exists. As the development of knowledge of an existing scientific field. This time researchers used qualitative research methods. In this method, the object is thoroughly or thoroughly researched with the intention of being in accordance with the thoughts of the researcher himself. The education policy at SDS Fadhilah is to facilitate children to get the best education by implementing school programs that support their interests and talents. Fadhilah Integrated Islamic SDS has excellent programs, from the curriculum field, namely project-based PTS, grade 6 comprehensive exams, and grade 6 munaqoshah exams. And from the student affairs sector, there are extra curricular activities that support and train children's talents. The curriculum implemented at Fadhilah Integrated Islamic School in the 2022/2023 academic year uses 2 curricula, the independent curriculum 1 for grades 1 and 4 and the 2013 curriculum for students in grades 2, 3, 5 and 6.